(untitled) (Journal of Science Foundation, 2013)
The experiment on wheat to zinc fertilization was carried out at the Regional Agricultural Research Station, Agricultural Research Sub-Station, and Special Crop Research Stations of BARI and at Farmers field. The grain yield was increased with increasing application of zinc upto 6 kg/ha but beyond that the level the yield was declined. The highest yield (3.87t/ha) was obtained in 6 kg Zn/ha under Amnura series as compare to Nachole and Lauta series. The lowest yield was obtained in Nachole series (3.07 t Zn/ha) under Deep Grey Terrace Soil. In Gangachara too, the grain yield of wheat was increased with increasing levels of zinc upto 6 kg Zn/ha beyond that it was declined. The highest yield (5.58t/ha) was obtained in 6 kg Zn/ha under Gangachara series and compare to Kaunia and Sonatola series. The lowest yield was obtained (3.92t/ha) in Kaunia series under Grey Floodplain Soils.The grain yield of wheat was significantly increased upto 12 kg Zn/ha in Calcarious Dark Grey Floodplain and Calcarious Brown Floodplain Soils and the order of increase was Zn12>Zn9>Zn6 >Zn3>Zn0. The highest yield (5.50 t/ha) was recorded in 12 kg Zn/ha. The order of the yield was Ishardi 5.50 t/ha > Sara5.47 t /ha> Gopalpur 5.13 t /ha>Darsona 2.91t/ha was recorded under Calcarious Dark Grey Floodplain and Calcareous Brown Floodplain Soils. DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14644 J. Sci. Foundation, 9(1&2): 15-25, June-December 2011